Herpes Zoster Ophthalmicus with Unilateral Blepharoconjunctivitis: Clinical Presentation and Management - Aulia Dewi Priwindrasari; Hermansyah Salim (PT Dexa Medica, 2025)
Introduction: Herpes zoster develops in individuals who have previously had chickenpox because both conditions arecaused by the same virus, the varicella zoster virus (VZV). After recovering from chickenpox, the virus remains dormant in the sensory ganglia and can reactivate when the immune system becomes weakened. Case: A 13-year-old girl presented with complaints of reddish bumps, which are reported to be itchy and painful, lasting for approximately 4 days. This patient has no history of varicella disease but exhibits symptoms of herpes zoster. Treatment is provided to suppress the progression of the disease, as well as to manage and prevent further complications. Conclusion: Herpes zoster ophthalmicus (HZO) results from the reactivation of the VZV in the ophthalmic branch of the trigeminal nerve. Individuals with weakened immunity, particularly older adults, are at higher risk. HZO can lead to various ocular complications such as conjunctivitis, blepharoconjunctivitis, keratitis, and uveitis. Early antiviral treatment can reduce the severity and duration of symptoms, prevent complications, and minimize the risk of postherpetic neuralgia. Proper management, including antiviral therapy, pain control, and eye care, is crucial to improve clinical outcomes.